A Coat of Many Colors Dress Culture in the Young State of Israel - Helman, Anat (Academic Studies Press, 2011)
A Coat of Many Colors investigates Israel's first seven years as a sovereign state through the unusual prism of dress. Clothes worn by Israelis in the 1950s reflected political ideologies, economic conditions, military priorities, social distinctions, and cultural preferences, and all played a part in consolidating a new national identity. Based on a wide range of textual and visual historical documents, the book covers both what Israelis wore in various circumstances and what they said and wrote about clothing and fashion. Written in a clear and accessible style that will appeal to the general reader as well as to students and scholars, A Coat of Many Colors introduces the reader both to Israel's history during its formative years and to the rich field of dress culture.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: History / Middle East / Israel & Palestine; History; Electronic books